Beyond physical exhaustion: Understanding overtraining syndrome through the lens of molecular mechanisms and clinical manifestation - Fiala, O.; Hanzlova, M.; Borska, L.; Fiala, Z.; Holmannova, D. (Sports Medicine and Health Science, 2025)
Background Overtraining Syndrome (OTS) is a condition resulting from excessive physical activity without adequate recovery, predominantly affecting elite athletes and military personnel. While overreaching can be a temporary state, non-functional overreaching may progress to chronic OTS. This review explores various hypotheses regarding the pathogenesis of OTS, including glycogen depletion, dysregulated cytokine response, oxidative stress, and alterations in the autonomic nervous system function. It also highlights the systemic impact of OTS on multiple organ systems, immune function, and overall health, linking the condition to chronic inflammation and an increased disease susceptibility. Additionally, it addresses the role of the gut microbiome in health modulation through physical activity.